On the interpretation of X-ray photoelectron spectra of Pt-Cu bimetallic alloys - Khalakhan, Ivan; Vorokhta, Mykhailo; Xie, Xianxian; Piliai, Lesia; Matolínová, Iva (Journal of electron spectroscopy and related phenomena, 2021)
•Overlapping the XPS Pt 4f and Cu 3p spectra of Pt-Cu alloys complicates its analysis.•XPS Cu 3p spectra were examined for all oxidation states of copper (Cu0, Cu+, Cu2+).•The Cu 3p spectra were then used for the precise fitting of Pt-Cu XPS Pt 4f spectra. The progress in the design of a perspective alloy catalyst relies on correct interpretation of its photoelectron spectra. Particularly, X-ray photoelectron spectroscopic (XPS) analysis of platinum-copper alloys represents a serious challenge for both qualitative and quantitative analyses due to the complexity of the Pt 4f spectra arising from its overlapping with the Cu 3p region. Studies regarding XPS investigation of Pt-Cu alloys often ignore the Cu 3p contribution while fitting Pt 4f spectra, which leads to partially incorrect interpretation of measured XPS data. This is most noticeable for alloys containing more than 50 % of platinum where the low-intensity Cu 3p core levels can be hidden under a more intense contribution of Pt 4f. In this work, we present the correct way of processing photoemission spectra of such systems. First, we thoroughly examine the XPS Cu 3p spectra of pure copper surfaces of different oxidation states, namely Cu°, Cu+, and Cu2+. Then, the obtained results are applied for the fitting of Pt 4f spectra of both metallic and oxidized Pt-Cu systems. The precise curve-fitting and data analysis procedure showcased in this study can be utilized to eliminate uncertainties in the analysis of Pt-Cu photoemission spectra.